Volatility of Returns in Stock Market Investments: A Study of BRICS Nations - N. Pankunni; S. Rajitha Kumar (Финансы: теория и практика, 2023)
Fluctuations in returns from investment in stocks make these risky. This factor should be kept in mind in stock investment decisions, which determines the relevance of this research. Through the study, the volatility in the stock returns of BRICS nations is analysed for inferring on the riskiness associated with investing in the respective nations, which is the aim of the research. For this study, the daily returns of five indexes representing each of the nation namely Ibovespa (Brazil), Moex (Russia), Nifty 50 (India), Hang Seng Index (HSI, China), and FTSE/JSE All Share Index (JALSH, South Africa) for a period of 14 years are collected and analysed. Both unconditional and conditional volatility in returns is analysed for each of the nations for imparting clearer and more comprehensive picture of the volatility in returns. Such an in-depth and long period analysis of volatility of the returns of the emerging BRICS economies is a novelty of the research that determined that no volatility model can be said as perfect for all economies for all time. The GARCH (1, 1) model was used to study for the returns of all the five indexes. The results of the study point out that the daily returns of all these indexes are heteroscedastic, implying presence of varying variance. Accordingly, the study м that the BRICS nations’ index returns are more volatile and riskier, and authors are recommended to invest in those indexes with lesser conditional volatility.